Folate‐/FAD‐dependent tRNA methyltransferase from Thermus thermophilus regulates other modifications in tRNA at low temperatures. (30th May 2016) - Yamagami, Ryota; Tomikawa, Chie; Shigi, Naoki; Kazayama, Ai; Asai, Shin‐ichi; Takuma, Hiroyuki; Hirata, Akira; Fourmy, Dominique; Asahara, Haruichi; Watanabe, Kimitsuna; Yoshizawa, Satoko; Hori, Hiroyuki
Abstract : TrmFO is a N 5, N 10 ‐methylenetetrahydrofolate (CH2 THF)‐/FAD‐dependent tRNA methyltransferase, which synthesizes 5‐methyluridine at position 54 (m 5 U54) in tRNA. Thermus thermophilus is an extreme‐thermophilic eubacterium, which grows in a wide range of temperatures (50–83 °C). In T. thermophilus, modified nucleosides in tRNA and modification enzymes form a network, in which one modification regulates the degrees of other modifications and controls the flexibility of tRNA. To clarify the role of m 5 U54 and TrmFO in the network, we constructed the trmFO gene disruptant (∆ trmFO ) strain of T. thermophilus . Although this strain did not show any growth retardation at 70 °C, it showed a slow‐growth phenotype at 50 °C. Nucleoside analysis showed increase in 2′‐ O ‐methylguanosine at position 18 and decrease in N 1 ‐methyladenosine at position 58 in the tRNA mixture from the ∆ trmFO strain at 50 °C. These in vivo results were reproduced by in vitro experiments with purified enzymes. Thus, we concluded that the m 5 U54 modification have effects on the other modifications in tRNA through the network at 50 °C. 35 S incorporations into proteins showed that the protein synthesis activity of ∆ trmFO strain was inferior to the wild‐type strain at 50 °C, suggesting that the growth delay at 50 °C was caused by the inferior protein synthesis activity. Abstract : We found that 5‐methyluridine at position 54 in tRNA contributes to maintain the appropriate modification degrees of 2′ ‐ O ‐methylguanosine at position 18 and N 1 ‐methyladenosine at position 58 in tRNA through the tRNA modification network in Thermus thermophilus .